Table of content and Editorial - Dinbabo, Mulugeta (African Human Mobility Review, 2021)
This issue consists of six articles. The first article by Ajwangâ€™ Warria entitled â€œStatelesstransnational migrant children in South Africa: Implications and opportunities forsocial work interventionâ€, examines statelessness in South African migrant childrenand conducts a literature review to clarify the phenomenon. This research assessesthe causes and circumstances that lead to statelessness among South African migrantchildren. The findings indicate that a large number of migrant children are at risk ofstatelessness in South Africa. This research contributes to the literature and debateson statelessness in childhood and highlights the potential role of social workers in addressing this important phenomenon. In general, this is South Africa's first researchon statelessness from a social work perspective and shows how transnational migration and national legislation can contribute to statelessness and put children at risk.